STUDY OF IMPLEMENTATION OF THE MINISTER OF LAW AND HUMAN RULES REGARDING REGISTRATION AND GIVING IMMIGRATION FACILITIES FOR DOUBLE CITIZENS - Intan Nurkumalawati (Polteknik Imigrasi, 2018)
This study is to analyse and review the implementation of the Law and Human Rights Minister’s Regulation about a registration and immigration facility for children with dual citizens’ status. Some problems arise as to provisions on the Law and Human Rights Minister’s Regulation Number 22 of 2012 on Procedures of a Registration for Children with Dual Citizens’ Status and Immigration Facility Application in accordance with the Law and Human Rights Minister’s Regulation Number 12247 of 2016 on Procedures of Indonesian Citizenship Application through an Electronic System. This study shows that the Law and Human Rights Minister’s Regulation needs areas of improvement pertaining to some categories of children with dual citizens’ status subject to the Indonesian Citizenship Law Number 12 of 2006, a compulsory registration for children with dual citizens’ status has yet no legal force and effect for those who violate it, no provisions regulate the validity of the certificate of registration but it is printed in the certificate and the card, and two terms “affidavit” and “immigration facility” may lead to ambiguity and have an effect on the process of citizenship status determination by someone who is at 18 or not exceeding 21 years old.